STUDI EMPIRIS PENGARUH EARNINGS DAN CASH FLOWS TERHADAP FUTURE CASH FLOWS PADA PERUSAHAAN YANG TERDAFTAR DALAM JAKARTA ISLAMIC INDEKS (JII) - Tito Marta Sugema Dasuki (MAKSI, 2015)
The purpose of this study is to test the ability of earnings information, the component of earning, and cash flows to predict future cash flows. This research is conducted by using the sample of firms that included the Jakarta Islamic Index (JII). Analysis method that used in this research is quantitative method with multiple regression. Sampling method that used is purposive sampling.Cash flow of the past affect the future cash flow significantly, it is the result of the accumulation effect of the components of cash flow (operating cash flow, investment cash flow and fund cash flows), which also has a significant influence on the future cash flows, while the profit has no effect on future cash flows. If the company has increased its earnings in a period, then the operating cash flow in subsequent periods may be increased. But the cash flow and cash flow of investment funds may be negative, because the company uses its profit to pay dividends, making investments and also paying its debts. This is why total cash flows are not necessarily positive.Key Word:Earning, Cash Flows,Regression.